Efeito da frequência de amamentação sobre a taxa de ovulação após tratamento com desmame temporário + GnRH, sobre a incidência de luteólise prematura no primeiro ciclo estral pós-parto e sobre o desempenho da progênie de vacas Nelore - Claro Junior, I. [UNESP]; Sá Filho, O. G. [UNESP]; Rodrigues Junior, M. M. [UNESP]; Vasconcelos, José Luiz Moraes [UNESP] (Universidade Federal de Minas Gerais (UFMG), Escola de Veterinária, 2010)
Avaliou-se o efeito da restrição na frequência de amamentação sobre o diâmetro folicular no dia 0 (DFOL), sobre a taxa de ovulação (TO), e sobre a incidência de luteólise prematura no primeiro ciclo estral pós-parto (ILP) de vacas Nelore multíparas, em anestro, submetidas à amamentação ad libitum (controle; n= 115) ou amamentação uma vez ao dia (restrito; n= 109), entre os dias -14 e 9 do experimento, e estudou-se o efeito desses tratamentos sobre o peso à desmama da progênie dessas vacas. Induziu-se ovulação com remoção de bezerros entre os dias -2 e 0 e aplicação de 100μg de GnRH no dia 0. Somente animais que ovularam foram mantidos no experimento (n= 125). A ocorrência de luteólise prematura foi avaliada por meio da dosagem da concentração sérica de progesterona nos dias 5 e 9. A TO não foi influenciada pelos tratamentos (55,8%; P>0,1), e as vacas do tratamento restrito apresentaram maior DFOL (10,90±0,26 vs. 10,18±0,21mm; P<0,05) e menor ILP (21,4% vs. 43,5%; P<0,05). Os bezerros do tratamento controle foram mais pesados (162,32±2,08 vs. 155,91±4,12kg; P<0,05). Conclui-se que a restrição na frequência de amamentação em vacas Nelore reduz a ILP, porém com possível efeito negativo no desenvolvimento dos bezerros.

The effects of restricted suckling on follicular diameter at day 0 (FDDO), ovulation rate (OR), and incidence of premature luteolysis in the first post partum estrous cycle (PLI) of Nelore cows and the effects on weight at weaning (WW) of progenie of these cows were evaluated. Multiparous anestrous postpartum Nelore cows were submitted to ad libitum suckling (control; n= 115) or once-a-day suckling (restricted; n= 109) from days -14 to 9 of the experiment. For both treatments, a temporary calf removal was performed from days -2 to 0, and on day 0 cows received 100μg of GnRH. Only animals that ovulated after GnRH treatment were used in the experiment (n= 125). The occurrence of premature luteolysis was evaluated by dosage of serum progesterone concentrations on days 5th and 9th. The OR was not affected by treatments (55.8%; P>0.1), but cows from restricted treatment had larger FDDO at time of GnRH treatment (10.90±0.26 vs. 10.18±0.21mm; P<0.05) and lower PLI (21.4% vs. 43.5%; P<0.05) than cows from control treatment. Calves from control treatment had higher WW than calves from restricted treatment (162.32±2.08 vs. 155.91±4.12kg; P<0.05). These results indicate that the restriction in frequency of suckling in Nelore cows may decrease the incidence of premature luteolysis in the first postpartum estrous cycle; however, with possible negative effects on calves development.
Effect of suckling frequency on ovulation rate after temporary weaning + GnRH treatment, incidence of premature luteolysis in the first postpartum estrous cycle, and performance of calves from Nelore cows
Keywords: amamentação restrita; taxa de ovulação; luteólise prematura; peso à desmama; beef cattle; suckling; ovulation rate; premature luteolysis; weight at weaning